Biopolitics at 50 years : founding and evolution - Wohlers, Tony; Fletcher, Amy (Emerald Publishing Limited, 2022)
Biopolitics at 50 Years: Founding and Evolution explores the study of biology and politics through the prism of fifty years of experience presenting current research that illustrates the nature and evolution of biopolitics. Containing substantive chapters that address many issues using different methodologies, Biopolitics at 50 Years draws on different theoretical perspectives to advance the field. Beginning with a reflection on the origin and scholarly emphasises of biopolitics and concludes with future prospects in the field, this 13th volume of Research in Biopolitics explores the broad scale theoretical consideration of politics based on evolutionary factors affecting the political realm physiological factors affecting political behavior, public policy issues affected by biology and how human nature affects outcomes of policy making.
Keywords: Biopolitics.; Political Science -- History & Theory.; Political science & theory.; elektronické knihy; electronic books